Digital Records Management Strategies to Support Transparent Administrative Governance - Nuraini Riauwati; Ayu Lestari; Fatimah Az Zahro (UIN Siber Syekh Nurjati Cirebon, 2026)
The rapid development of information technology has encouraged the transition of records management from conventional systems to digital systems, particularly to enhance administrative transparency in educational institutions. Digital records serve not only as tools for information storage but also as instruments of accountability and decision-making. However, the implementation of digital records management still encounters several challenges, including limited technological infrastructure, inadequate human resource competencies, the lack of integrated archival policies and regulations, and weak management procedures. This study aims to examine the challenges and strategies of digital records management and its role in promoting administrative transparency in the education sector. The research employs a qualitative approach through a literature review by analyzing relevant books, scholarly articles, and regulations. Data analysis is conducted using the interactive model proposed by Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The findings indicate that effective digital records management strategies include strengthening digital archival policies and regulations, utilizing integrated electronic records management systems, enhancing human resource competencies, and implementing clear standard operating procedures. These strategies contribute to improving information openness, expanding public access, and strengthening administrative auditability. The study concludes that well-planned and integrated digital records management is a crucial factor in achieving transparent, accountable, and efficient administrative governance in educational institutions. Keywords: digital records, administrative transparency, records management, educational institutions.